The roles of remote sensing in nature conservation : a practical guide and case studies - Díaz-Delgado, Ricardo; Lucas, Richard; Hurford, Clive (Springer, 2017)
During recent decades, a rapid increase in available data sources has enabled researchers to develop hundreds of new remote sensing applications: data provided by new sensors attached to satellites, aircrafts and drones. However, a major challenge remains unresolved: how to transfer the knowledge of these technological advances to conservation practitioners and facilitate access to the remote sensing products that are currently available. In this volume, we illustrate the ability of new technologies, such as drones, camera traps or miniaturized sensors, to enhance our information on habitat condition, species occurrence, invasive species mapping or biodiversity. There are several case studies from Natura 2000 and LTER sites: these were designed to meet the requirements of the EC Birds and Habitats Directives and the commitments associated with the EU Biodiversity Strategy, including regular habitat assessments. The authors of this volume, who work for different conservation and research agencies, provide a practical perspective on how remote sensing applications can benefit these long-term monitoring or surveillance programs. With these requirements in mind, the time is now right for conservation ecologists, researchers, technicians, managers, policy makers and practitioners to embrace the new technologies and products that are available from the remote sensing community.
Keywords: Ecology -- Remote sensing.; Nature conservation.; elektronické knihy; electronic books